2015
DOI: 10.1016/j.physletb.2015.02.056
|View full text |Cite
|
Sign up to set email alerts
|

Gravitational Aharonov–Bohm effect due to noncommutative BTZ black hole

Abstract: Editor: M. Cvetič In this paper we consider the scattering of massless planar scalar waves by a noncommutative BTZ black hole. We compute the differential cross section via the partial wave approach, and we mainly show that the scattering of planar waves leads to a modified Aharonov-Bohm effect due to spacetime noncommutativity.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 62 publications
0
24
0
Order By: Relevance
“…By using the Hamiltonian approach and/or the counterterm method, one can find the total mass of the solutions as 16) in which by evaluating metric function on the horizon (f (r = r + ) = 0), we obtain M = −Λr 2 + + m 2 r + cc 1 − 2q 2 ln r + l . The electric potential, U , is defined through the gauge potential in the following form…”
Section: Thermodynamicsmentioning
confidence: 99%
“…By using the Hamiltonian approach and/or the counterterm method, one can find the total mass of the solutions as 16) in which by evaluating metric function on the horizon (f (r = r + ) = 0), we obtain M = −Λr 2 + + m 2 r + cc 1 − 2q 2 ln r + l . The electric potential, U , is defined through the gauge potential in the following form…”
Section: Thermodynamicsmentioning
confidence: 99%
“…The partial wave approach has been widely applied in the black hole scattering process by considering various types of metrics . This approach has also been applied to exploit scalar wave scattering by acoustic black holes [44][45][46][47][48][49][50][51] and also in [52] the differential cross section of a noncommutative BTZ black hole has been obtained. In our analysis we have initially calculated the phase shift analytically and then computed the differential cross section and the absorption.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the fact that these solutions being asymptotically AdS, there has been various studies regarding AdS/CFT correspondence [21][22][23] . In addition, the noncommutative geometry in three dimensions has been of interest recently [24][25][26][27][28][29] and it was shown that gravitational Aharonov-Bohm effect could be originated from noncommutative BTZ black holes [30]. Moreover, in order to obtain quantum aspect of three dimensional gravity, entanglement and quantum loop entropy of the BTZ black holes have been investigated in literatures [31][32][33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%